A Comparative Analysis of the Efficacy of Mulligan Bent Leg Raising Versus Slump Stretching Combined with SWD in Mechanical Low Back Pain - Okkagani Berranghi Obuun (Multidisciplinary Journal of Akseprin Indonesia, 2025)
The problem statement: Low back pain (LBP) is the most prevalent, self-reported form of musculoskeletal pain, frequently recurrent, and carries significant socio-economic implications. Approximately eighty percent of low back pain is attributed to "mechanical back pain," resulting from muscle strain or ligament tear in the back. The muscular strain and ligament sprain result from abrupt, unfamiliar exercises and incorrect posture. Methodology: The participants were recruited through Sri Venkateshwaraa Medical College Hospital and Research Centre, Ariyur, Pondicherry-605 102. The objective of the study was to evaluate the efficacy of Mulligan Bent Leg Raising (MBLR) compared to Slump Stretching combined with SWD in alleviating pain and enhancing Straight Leg Raise (SLR) in cases with mechanical low back pain. Outcomes: The statistical analysis derived from the unpaired t-test indicates that the post-test values for range of motion and pain in Group A and Group B are 5.39 (p < 0.001) and 5.43 (p < 0.001), respectively. The statistical study revealed a considerable difference between Group A and Group B, with Group A demonstrating more effectiveness. The study concluded that the Mulligan bent leg raise, in conjunction with SWD, was beneficial in treating mechanical low back pain in college students